Protonation and Photocatalytic Activity of the Rb2La2Ti3O10 Layered Oxide in the Reaction of Hydrogen Production. (20th December 2017) - Rodionov, Ivan A.; Sokolova, Iuliia P.; Silyukov, Oleg I.; Burovikhina, Alena A.; Fateev, Sergey A.; Zvereva, Irina A.
Abstract : The Rb2 La2 Ti3 O10 layered oxide was synthesized by the solid-state method. Three phases with different protonation degrees and intercalated water contents were obtained from the initial compound by the treatment with distilled water and hydrochloric acid. The obtained samples were characterized by powder X-ray diffraction, SEM, X-ray microanalysis, BET, DRS, and TG. It was found that the complete ion exchange of Rb + for H + in the layered oxide Rb2 La2 Ti3 O10 proceeds through the formation of two metastable intermediate phases with average protonation degrees of 0.5 and 0.75, which successively transform from one to another. Each of these phase transformations is accompanied not only by the contraction of the interlayer distance but also by the displacement of adjacent perovskite layers by 1/2 of the cell parameter which results in the change in the space group. The photocatalytic activity of obtained samples decreases with the increase in the protonation degree, which correlates with the decrease in the intercalated water content.